Pengaruh Likuiditas Dan Kepemilikan Institusional Terhadap Nilai Perusahaan Dimoderasi Oleh Kebijakan Dividen - Puja Wijaya, Ida Bagus Nyoman; Purnawati, Ni Ketut (E-Jurnal Manajemen, 2014)
This study aim to examine effect of liquidity and institutional ownership on firm value moderated by dividend policy. The sample used 32 manufacturing companies listed on Indonesia Stock Exchange during the period 2009-2012. Analysis technique use multiple linear regression and moderated regression. The result show that liquidity has significant negative effect on firm value, institutional ownership has no significant effect on firm value, dividend policy can not moderate the relationship of liquidity and institutional ownership on firm value. Keywords: liquidity, institutional ownership, dividend policy, firm value